A follow up study of warning letters issued by US Food and Drug Administration to clinical investigators, institutional review boards and sponsors: a situational analysis during COVID-19 pandemic - Y. C., Shetty; Sethi, Meher; Barsinge, Tanvi; Kamath, Yash; A. S., Kulkarni (International Journal of Research in Medical Sciences, 2025)
Background: United States food and drug administration (FDA) is the apex body governing and regulating clinical research. FDA issues warning letters (WLs) to individuals and institutions for significant regulatory violations. Our study aimed to evaluate the WLs issued to various stake holders during COVID-19 pandemic. Methods: A web-based analytical study was employed to analyse WLs issued between 01 January 2020 to 31 December 2022 to clinical investigators, institutional review board (IRB) and sponsors. The outcome measures were: total number of WLs, violation theme and trend analysis in comparison with the previous study. Results: A total of 241 WLs were analyzed which included 232 (96.27%) letters to sponsors, 9 (3.73%) to clinical investigator and none to IRB. Device-related violations were failure to comply with current good manufacturing practice (CGMP) (26/39, 66.67%; 8/14, 57.14%), adulterated/misbranded products (19/39, 48.71%; 7/14, 50%) and failure to follow monitoring schedule (16/39, 41.02%; 5/14, 35.71%) in 2020 and 2022 respectively. While in 2021, failure to submit investigational device exemption (50/61, 81.87%) was the commonest theme. In the drug-related group, violation trends were similar for 2020, 2021 and 2022. The frequent violations were misbranded/unapproved drug (24/26, 92.3%; 15/21, 71.43%; 40/57, 70.17%) and failure to comply with CGMP (8/26, 30.77%; 8/21, 38.09%; 19/57, 33.33%). Our previous study of 2015 is at variance, highlighting deviations as failure to follow monitoring schedule, failure to obtain investigator agreement and failure to maintain data record. Conclusions: Majority warning letters were issued to sponsors, pertaining to quality and process of drug and device related research.